How to Minimize Economic Loss in Future Pandemic? A Trend Analysis Based on the Role of AI Technology - Danish Mahmud (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
The COVID-19 pandemic revealed the vulnerability of global economies to health crises, highlighting the need for innovative solutions. This study explores how Artificial Intelligence (AI) can reduce the financial impact of pandemics across healthcare, supply chains, and economic forecasting. Using trend analysis, it shows how AI technologies—such as predictive analytics, automation, and optimization—enhance decision-making and support continuity in health and business sectors. AI aids in virus spread forecasting, efficient resource allocation, and faster precision medicine, helping mitigate both immediate and long-term economic consequences. The research underscores the urgency of investing in AI infrastructure and regulatory frameworks to prepare for future crises. Ultimately, AI is shown not only to support pandemic response but also to lay the foundation for sustainable economic recovery and resilient societies.